(untitled) - Business School of the National Economics Univ. of Hanoi (Thành phố Hồ Chí Minh, 2001)
This book has been developed for owners and managers of small and medium enterprises (SMEs). As a small business owner or manager, you are involved in many aspects of running a business. Within this program, one series of workbooks focuses on the key aspects of human resource management.
Keywords: Job analysis,Personnel management